2013
DOI: 10.1007/s12665-013-2833-x
|View full text |Cite
|
Sign up to set email alerts
|

Recycling waste from natural stone processing plants to stabilise clayey soil

Abstract: For the countries with a developed stone industry the waste generated in the natural stone processing plants pose environmental and economic problems. The utilisation of stone waste in various areas is still under research. In addition, there are only a limited number of studies concerning the use of stone waste obtained from processing plants in the stabilisation of clayey soil. Furthermore, none of the studies in the literature investigated the effect of the characteristics of the stone on the stabilisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 11 publications
(9 reference statements)
4
30
0
Order By: Relevance
“…The liquid limits and plasticity indices of the treated soil samples decreased with their WMF contents, in alignment with the results of Sivrikaya et al (2014) and Baser (2009) on expansive soils. Although Sivrikaya et al (2014) and Baser (2009) reported an increase in the plastic limits of the expansive soil with increasing marble dust, the plastic limits of the treated lateritic clay samples were not significantly affected by increasing their WMF contents.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The liquid limits and plasticity indices of the treated soil samples decreased with their WMF contents, in alignment with the results of Sivrikaya et al (2014) and Baser (2009) on expansive soils. Although Sivrikaya et al (2014) and Baser (2009) reported an increase in the plastic limits of the expansive soil with increasing marble dust, the plastic limits of the treated lateritic clay samples were not significantly affected by increasing their WMF contents.…”
Section: Discussionsupporting
confidence: 88%
“…Although the soil considered by Sivrikaya et al (2014) is not lateritic, the effect of adding marble dust to the expansive soil on its compaction characteristics is similar to that obtained for this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, up to 25-30 % of screenings from crushing granite is produced during the manufacturing of coarse aggregate [1]. In addition, the granite dust (GD) with a grains size less than 0.16 mm is formed when screenings screening on narrow fractions in production process of graded sand as well as during working of dust collection systems of crushing and screening equipment.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. These materials could also be used in the construction of housing, public buildings and roads and thus their consumption in this area is another solution for the waste adsorbents [8,10].…”
Section: Introductionmentioning
confidence: 99%